Supporting users tasks with personal information management and web forms augmentation - Firmenich, Sergio Damián
Currently, most tasks performed by Web users require them to provide information. It is usual that several Web applications require similar information and users have to repeat the same information many times. However, Web forms are only the top of the iceberg of these problems users experience. First, Web forms have an intrinsic complexity such as users comprehension of Web forms input, data format for being used in Web forms input, etc. On the other hand, there are a lot of situations in which Web forms are not necessarily a problem for users but the problem resides in the information needed by Web forms. Repeating the same tasks - with the same information - in several Web sites, or using information from a Web site to fill forms in another one, are problems that users usually have to face with. In this work we analyze user's interactions with Web forms and propose an approach for enhancing Web forms using client-side adaptation techniques. As the use of Web forms is closely related to the management of personal information our approach includes the support for date exchange between user's personal information management systems (PIMS) and third-party Web forms. The approach is illustrated by a set of client-side adaptation tools and a pervasive Personal Information Management Systems called PIMI.